Concept of Index of Information Society Development Effects (IISDE) - Piotr GUTOWSKI; Ewelina GUTOWSKA (Communications of International Proceedings, 2021)
The world of today witnesses the expansion and adoption of digital technologies. They in fact take the industrial, economic and social space quite rapidly. Information societies have emerged, in which handling information has become the main production factor. One of their basic assumptions is transferring the economic gravity center to the sector of modern services. Large corporations, international organizations and governments, as they are aware of this state of affairs, try to stimulate and direct this process to achieve the greatest economic and social benefits as quickly as possible. Useful in these activities are effective measures in the form of complex indicators that provide knowledge about the current level of phenomena. The authors of this paper propose an indicator that can be used to identify the level of IS development. An innovative approach is to monitor the effects of building a civilization of knowledge rather than its determinants. This authenticates the reliability of result, because given the multidimensional nature and complexity of the phenomenon of building information societies, any identification of causal forces seems to be incomplete and very difficult to measure effectively.
Keywords: Information Society; Knowledge Civilization; Composite Indicators.